Endoscopic Ultrasound-guided Fine Needle Aspiration for the Diagnosis of Duodenal Stenosis Due to Urothelial Carcinoma - Motoo, Iori (Intern Med, 2020)
Upper tract urothelial carcinoma (UTUC) initially presents with hematuria and hydronephrosis. We report a case of UTUC presenting with initial findings of duodenal stenosis before the appearance of hydronephrosis. A 59-year-old man presented with upper abdominal symptoms on his initial visit. Esophagogastroduodenoscopy (EGD) revealed circumferential stenosis at the descending part of the duodenum. However, the underlying cause of duodenal stenosis was unknown as repeated histopathological examinations of endoscopic biopsy specimens showed no specific findings. We then performed endoscopic ultrasound-guided fine needle aspiration (EUS-FNA) of the thickened duodenal wall, and successfully diagnosed duodenal metastasis of UTUC. EUS-FNA is an effective diagnostic method in cases in which the cause of duodenal stenosis is unknown.